2003
DOI: 10.1029/2003gl018532
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale eddies in the South China Sea observed with altimeter data

Abstract: A composite time series (1993–2000) of sea surface height anomaly from several satellites is used to identify eddies in the South China Sea (SCS). The eddy lifetime, radius, strength, and straight‐line travel distance are estimated. Altogether 58 anticyclonic eddies and 28 cyclonic eddies are identified for this period. They are grouped into four geographical zones according to known eddy generation mechanisms, and their statistics are discussed accordingly. Our geographical classification is a useful first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
288
4
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(313 citation statements)
references
References 13 publications
19
288
4
2
Order By: Relevance
“…According to the eddy generation mechanisms, eddies in the SCS are grouped into four geographical zones by Wang et al [2003b], and their statistical characteristics are well documented in subsequent studies by Xiu et al [2010]. Modeling results by Chu et al [1998] indicated wind effect in generating the SCS deep eddies.…”
Section: Introductionmentioning
confidence: 88%
“…According to the eddy generation mechanisms, eddies in the SCS are grouped into four geographical zones by Wang et al [2003b], and their statistical characteristics are well documented in subsequent studies by Xiu et al [2010]. Modeling results by Chu et al [1998] indicated wind effect in generating the SCS deep eddies.…”
Section: Introductionmentioning
confidence: 88%
“…Its cross-section temperature, salinity and density characters show that the isotherm and isopycnal of 18°N cross-section appeared to be high in the west and low in the east, both at surface and sub-surface Influenced by the monsoon, the Kuroshio intrusion and complex topography, a large amount of eddies are generated in the SCS, especially the anti-cyclonic warm eddies in the northern SCS [44][45][46]. However, these eddies are seldom captured by in-situ observations.…”
Section: Interannual Variability Of the Scswbcmentioning
confidence: 99%
“…The synergy of satellite observations and model simulations indicates that the high-frequent sea level variations in deep basin are mainly attributed to flow instabilities and tend to propagate along high-variance bands (Zhuang et al, 2010). The geographical distributions and tracks of eddies are firstly depicted by Wang et al (2003b) based on a merged altimetry dataset. Following this work, recently Xiu et al (2010) describe various eddy characteristics in the SCS using numerical study and show the westward tendency of eddy trajectories.…”
Section: Introductionmentioning
confidence: 99%